Pengaruh Metode Pembelajaran dan Etos Belajar terhadap Hasil Belajar Matematika Siswa - Desy Arsanty (JKPM (Jurnal Kajian Pendidikan Matematika), 2015)
The purpose of this study was to determine the influence of teaching methods on the results of students' mathematics learning, learning ethos influence on the results of students' mathematics learning, and interactive effects of learning methods and ethos of learning on students' mathematics learning outcomes. The method used in this research is the method of experiment. Population in this research is the students of class VII are limited to SMP 220 and SMP 127, District kebon jeruk academic year 2014/2015 as many as 48 students. The method used in this research is multimedia-based methods and conventional methods. The sampling technique used is the technique of random sampling. The research instrument used is an objective test form as much as 30 items tested its validity with the reliability coefficient = 0.780; questionnaires ethos of learning as much as 30 items that have been tested with the validity reliability coefficient = 0.861. Analysis of data using analysis of variance (ANOVA) two lanes. Results of hypothesis testing and analysis of data processing obtained the following conclusions: 1) There is a significant influence on the teaching methods of mathematics student learning outcomes. 2) There is a significant effect on the ethos of learning mathematics student learning outcomes. 3) There were no significant interaction effects of learning methods and ethos of learning on students' mathematics learning outcomes.